Overcoming the barriers to better evidence generation from clinical trials - Kehoe, L; Locke, T; McClellan, M; Hernandez, A; Landray, M; Okun, S (BioMed Central, 2024)
Clinical evidence generation from and for representative populations can be improved through increased research access and ease of trial participation. To improve access and participation, a modern trial infrastructure is needed that broadens research into more routine practice. This commentary highlights current barriers, areas of advancement, and actions needed to enable continued transformation toward a modern trial infrastructure for an improved evidence generation system. The focus of this commentary is on the development of medical products (e.g., drugs, devices, biologics) and infrastructure issues within the United States, with the aim to have broader, multi-national applicability.